Historical analysis of special economic zones in Russia - I. R. Tazutdinov (Путеводитель предпринимателя, 2020)
The article casts light upon the history of special economic zones in Russia, providing its periodization from the ancient times to the present time. The author focuses on some prototypes of modern Russian SEZs finding certain successive links between them. He analyses the main factors which have been determining the development of SEZs at different stages as well as the changes in the government’s economic policy approach towards such projects.